Self-evaluation of medical students on the elective research course - Rasidah Abdul, Wahab; Zunika, Amit (Medical Education Department, School of Medical Sciences, 2014)
The significance of learning research methodology and performing research has been accepted by various medical schools in Malaysia as well as in other countries. The aim of integrating research into medical curriculum is to inculcate the research culture and form part of the evidence-based practice among medical professionals. Hence, the Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak has incorporated the research component into the preclinical year of the medical curriculum. A survey was conducted to gauge the second year medical students’ level of knowledge of research process at the end of the course using a set of questionnaires. Seventy nine of second year medical students participated in the study. The outcome of the study shows significant improvement in the students’ knowledge on research components after completing the one year course (p<.05). Our findings suggest that the course has met its main objectives to make the students better understand the research processes. It is recommended that further evaluation should be conducted to refine the course.